EXAMINING THE INFLUENCE OF ONLINE SPACES ON PSYCHOLOGICAL WELL-BEING, CULTURAL IDENTITY, AND ELT PRACTICES: A QUANTITATIVE ANALYSIS (Al-Aasar, 2025)
Online spaces such as social media, forums, web journals, and online courses have gained significant influence in the 21st century, presenting both opportunities and challenges in communication, learning, and well-being. These “online spaces” serve as rich sources of English knowledge, “psychological well-being,” and culture for English language teachers and students. However, they may also expose individuals, particularly young learners, to false information, prejudice, and online bullying. Understanding the interplay between users' psychology, culture, and “ELT practices” is therefore essential. This study explores the effects of online environments on the “psychological well-being,” “cultural identity,” and “ELT practices” of English language teachers and students from diverse backgrounds. Using a quantitative methodology, data was collected and analyzed from 100 participants, including 50 English language instructors and 50 students who engage with “online spaces” for personal or professional purposes. A questionnaire was utilized, and results were processed using SPSS software. The study examines online spaces, cross-cultural communication, and “ELT practices” in digital environments. Findings reveal that online environment impact participants' “psychological well-being” in both positive and negative ways, influencing factors such as “self-efficacy,” “motivation,” “anxiety,” and “satisfaction.” Additionally, results indicate that online spaces shape participants’ “cultural identity” by either strengthening or diminishing their sense of belonging, awareness, and diversity. Furthermore, findings demonstrate that online environments affect “ELT practices” through their influence on teaching approaches, materials, and assessments. The study emphasizes the need to enhance the effectiveness of online platforms for English language instruction and learning. It suggests that “online spaces” should be strategically designed and utilized to foster instructional innovation, intercultural competence, and psychological support for English language teachers and students. Lastly, the study highlights its limitations and proposes directions for future research.